How mindfulness-based training improves stress-related health: a selective review of randomized clinical trials comparing psychological mechanisms of action - Puhlmann, Lara M. C.; Engert, Veronika (Frontiers in Endocrinology, 2025)
Mindfulness-based interventions (MBIs) have been shown to reduce both subjective experiences and physiological markers of stress, a central pathway to improving health and wellbeing. Yet, understanding of the causal mechanism through which MBIs affect stress-related health outcomes remains poor. Most MBIs rely on training programs that simultaneously target multiple and distinct mental processes, hampering mechanistic conclusions. Addressing this shortcoming, the present selective review provides an overview of randomized controlled trials (RCTs) that directly contrast the effects of distinct components of mindfulness on stress-related health. We examine two comparative frameworks, the prominent Monitor and Acceptance Theory (MAT) and the ReSource training program, an intervention protocol designed to disentangle mindfulness components in a large-scale mental training project. We focus on how a) attention monitoring and b) experiential acceptance skills affect the stress-related outcomes assessed. These include subjective-psychological stress and affect, and physiological stress and stress-related health markers (e.g., activity of the autonomic nervous system, the hypothalamic-pituitary-adrenal axis and proinflammatory activity), each in two different states of the stress system: acutely stressful challenges and more long-term basal functioning. In line with MAT, we find that monitoring needs to be coupled with acceptance for beneficial effects on stress-related physiological activity in states of acute challenge. In basal states, however, physiological stress activity can be buffered by monitoring alone, especially if practiced for longer duration. We suggest that when dealing with basal longer-term stress, monitoring allows individuals to use coping mechanisms other than acceptance, such as social support. Subjective-psychological stress and affect were mostly assessed in basal states and show either non-specific effects after all types of training, or are most affected by combined monitoring and acceptance. Our work highlights the need to evaluate different training mechanisms in relation to stress-specific states (herein, basal versus challenge) and outcomes (herein, subjective-psychological versus physiological) in order to better understand mindfulness mechanisms of action.